The 'spirit of sport', WADAs code review, and the search for an overlapping consensus. Issue 2 (3rd April 2019) - Loland, Sigmund; McNamee, Michael J.
ABSTRACT: In this paper, we argue for the recognition that anti-doping is in itself first and foremost an ethical position. The current World Anti-doping Code formulation of 'the spirit of sport' is an acknowledgement of this point and a counterweight against scientific and technicist understandings of the nature of anti-doping itself. We critically review the Code formulations on 'the spirit of sport'. Based on a theoretical background of various approaches to normative agreement and consensus in a setting of diversity of 'comprehensive views', we argue for revision of the Code. Specifically, we argue for a re-formulation of 'the spirit of sport' in terms of athlete protection and the preservation of the integrity of sporting competition that could meet requirements on an overlapping consensus among all WADA stakeholders. This is not just a matter of formality and Code acceptance. An overlapping consensus is not a mere modus vivendi but a normative consensus based on fair, honest, and transparent discourse in which participants deliberate in a setting of mutual respect and trust, and of 'decency', which is a basis for a consensus that cultivates authentic stakeholder commitment.